Development of Muscle Explosive Power Tests on Upper Body - Qory Jumrotul Aqobah; Reqgi First Trasia; Masnur Ali; Adito Joyo Ari Pratama (Universitas Negeri Semarang, 2024)
Tests and measurements in the field of sports are important to reach the peak of achievement. With advances in technology in the field of sports can help make it easier to carry out tests and measurements. Upper muscle explosive power (upper body) is one important component to achieve achievement in each sport. The results of observations in the field, tests and measurement of upper muscle explosive power are still using manuals not digitally, such as push up Ball uses a measuring instrument in the form of a long ruler or meter. The method used in this study is the Research & Development (R&D) method that refers to the 4D model of the development of Thiagaradjan & Semmel with steps including Define, Design, Develop, and Disseminate. The research subjects are athletes who will compete in the 2024 National Sports Week (PON) Banten Province and its surroundings. Data collection methods are carried out using media and material validation questionnaires. Data analysis techniques use descriptive statistics that refer to the guide of Mardapi (2018), namely by converting score data on the questionnaire sheet into a qualitative form, calculating the average score of the total filling of the questionnaire sheet, and changing the average score into a qualitative value. The results show that it is very practical as indicated by the results of the questionnaire and has good effectiveness on training results.